REALISME MAGIS DALAM CERPEN: KASUS CERPEN GABRIEL GARCIA MARQUEZ, TRIYANTO TRIWIKROMO, DAN A.S. LAKSANA - Imam Muhtarom (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2014)
Magic Realism Prose brings the magic and the reality at once in a narration. Reality and magic have mutual support to build a narration. The support between the reality and the magic is not only manifested in the unity of the narration but also gives the possibility to give the meaning that goes beyond the narration itself. In other words, the meaning also gives the magic realism experience for the readers. This paper will analyze the form of magic realism in Gabriel Garcia Marquez’s short story entitled “Light is Like Water”, Triyanto Triwikromo’s short story entitled “Sayap Kabut Sultan Ngamid”, and A.S. Laksana’s short story entitled “Dongeng Cinta yang Dungu”.Keywords: real, magic, prose, magic realism.